Can carbon labels shift consumers towards sustainable food? Evidence from Chinese consumers - Yalin Xu; Zhiwen Zhang; Yanjun Ren; Rong Yuan; Yanan Wang; Rui Li; Shunan Zhao; Lu Qiu (Sustainable Futures, 2024)
Carbon labels are becoming an essential tool for policymakers in many countries to promote low-carbon consumption. To assess customers' willingness to pay for five carbon-labeled agricultural products (CAP), we used payment card to conduct a questionnaire survey among 641 respondents in Shanghai, Nanjing, Wuhan, and Xi'an, all located in China. This study quantitatively analyzes the influencing factors and interactive mechanisms of the public's willingness to purchase CAP through the extended Theory of Planned Behavior and Norm Activation Model. The results show that consumers' willingness to pay a premium for carbon-labeled milk, corn, bananas, tomatoes, and eggs is 27.50 %, 29.73 %, 26.86 %, 26.51 %, and 24.26 % respectively. Perceived behavioral control has the strongest positive influence on purchase intention, followed by subjective norms, attitudes toward the behavior, and personal norms. There is a significant mediating effect between awareness of consequences and personal norms, which indirectly influences personal norms through the ascription of responsibility and subsequently affects purchase intention. Additionally, there is a gap between purchase intention and behavior, and risk perception negatively moderates the relationship between the two. Based on the research findings of this paper, practical and effective policy suggestions are proposed for the government to promote carbon labeling policies and reduce carbon emissions.
Keywords: 330; carbon-labeled agricultural products; willingness to pay; Theory of Planned Behavior; Norm Activation Model; China